Fractal bodies invisible in 2 and 3 directions - Plakhov, Alexander (2013)
We study the problem of invisibility for bodies with a mirror surface in the framework of geometrical optics. We show that for any two given directions it is possible to construct a two-dimensional fractal body invisible in these directions. Moreover, there exists a three-dimensional fractal body invisible in three orthogonal directions. The work continues the previous study in [1, 12], where two-dimensional bodies invisible in one direction and three dimensional bodies invisible in one and two orthogonal directions were constructed.